Integrated Business Planning How to Integrate Planning Processes, Organizational Structures and Capabilities, and Leverage SAP IBP Technology - Kepczynski, Robert (Management for Professionals,, 2018)
This book presents a comprehensive introduction to Integrated Business Planning (IBP), building on practitioner's experience and showcasing the value gains when moving from disconnected planning to IBP. It also proposes a road map for the transformation of planning, including technological initiatives, business priorities and organizational processes, and demonstrates how to motivate different IBP stakeholders to work together, when and how to connect strategic, tactical and operational planning and how to leverage functional and data integration features of SAP IBP. Real-world business-process use cases help to show the practical implications of implementing SAP IBP. Furthermore the book explores new capabilities, including chapters on talent acquisition and retention, and career development leadership in an IBP Center of Expertise. A discussion of how disruptive technology trends like big data, Internet of Things, machine learning and artificial intelligence can influence IBP now and in the near future rounds out the book.